The Effect of Garlic Extract (Allium sativum) on Marination of Native Chicken Meat on Cooking Loss, Water Holding Capacity, Tenderness and Organoleptics - Herlia, Andrea; Suryaningsih, Lilis; Gumilar, Jajang (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Native chicken meat has a tougher texture, so it requires a longer processing time. Native chicken meat used in this study come from 6 month old female native chicken meat. Garlic contains compounds with high antibacterial and antioxidant activity, so it can be used as a natural preservative to maintain meat quality and affect its physical properties of meat including texture. This study aims to determine the effect and best concentration of using garlic extract (Allium sativum L.) on cooking loss, water holding capacity, tenderness and organoleptic of native chicken meat. The study was conducted at the Animal Product Processing Technology Laboratory and at the Biotechnology Research and Testing Laboratory, Faculty of Animal Husbandry, Padjadjaran University. The study was conducted using an experimental method using a completely randomized design with 5 treatments and 4 replications. Marinating treatments using various concentrations of garlic extract consisted of P0 (without marination), P1 (10%), P2 (20%), P3 (30%) and P4 (40%). The parameters cooking loss, water holding capacity and tenderness were analyzed using Analysis of Variance and Duncan's further test, while organoleptic data were analyzed using Kruskal Wallis and Mann Whitney. The results showed that the treatment had a significant effect (P<0.05) on water holding capacity and tenderness but gave results that had no significant effect on cooking losses and organoleptics. The best treatment was P3 (30%) with a cooking loss value of 35.10%, water holding capacity of 36.828%, tenderness of 2.169 kgf and organoleptic properties favored by the panelists.